Structural elucidation and anti-nonalcoholic fatty liver disease activity of Polygonatum cyrtonema Hua polysaccharide. Issue 24 (28th November 2022) - Liu, Wei; Shao, Taili; Tian, Lei; Ren, Zhengrui; Gao, Lan; Tang, Zhiyan; Fang, Zheng; Yuan, Pingchuan; Liu, Chunyan; Li, Jikun; Wang, Guodong; Han, Jun
Abstract : A structurally novel polysaccharide from Polygonatum cyrtonema Hua, PCP-1, can improve abnormal lipid metabolism and oxidative stress, and balance the composition of the intestinal microbiota in non-alcoholic fatty liver disease (NAFLD) mice. Abstract : The chemical structure and pharmacological activity of Polygonatum cyrtonema Hua polysaccharides have garnered significant attention in recent years. In this study, a homogeneous polysaccharide, PCP1, was extracted from P. cyrtonema Hua rhizomes and purified. Monosaccharide composition analysis showed that PCP1 is primarily composed of fructose, glucose, and mannose. Chemical structure analysis showed that the main chain of PCP1 is composed mainly of →1)-β-d -Fru f -(2→ and →1, 6)-β-d -Fru f -(2→, with small amounts of →6)-α-d -Glc p -(1→, →4)-β-d -Man p -(1→, and β-d -Glc p -(1→. The side chain is β-d -Fru f -(2→ linked at C-6 of →1, 6)-β-d -Fru f -(2→. In vivo experiments showed that PCP1 mitigates liver pathological damage, improves abnormal lipid metabolism and oxidative stress, promotes the production of short-chain fatty acids, and balances the composition of the intestinal microbiota in non-alcoholic fatty liver disease (NAFLD) mice. Thus, PCP1 can be used as a natural ingredient in functional foods for the treatment of NAFLD.